Trend analysis of precipitation and temperature in Lahaul-Spiti district, Himachal Pradesh, India - Kumar, Pankaj; Deka, Dhanjit; Husain, Md. Arif; Kumar, Manish; Choudhari, Pandurang; Singh, Shipra; Kamil, Azka; Banerjee, Abhishek (Frontiers in Climate, 2025)
Lahaul-Spiti district is a cold desert mountain, situated in the Trans-Himalayan region. The district has the lowest population density of 2 persons/km2 because of the harsh climate and rough topography that act as barriers to population growth. Specific knowledge of climate variability in the region is limited. Hence, it is essential to study the trends of temperature and precipitation for the region and also its effects on sustainable development. The objective of this study is to investigate the variability of rainfall and temperature on a monthly, seasonal, and annual basis from 1981 to 2021. Precipitation and temperature data on a monthly, seasonal, and annual basis were acquired from the National Aeronautics and Space Administration (NASA) Langley Research Center’s POWER Project. The trends of precipitation and temperature were derived using the Mann–Kendall trend test and the slope of the regression line using Sen’s slope test. Subsequently, the maximum, minimum, mean, standard deviation (SD), and coefficient of variation (CV) of precipitation and temperature were computed to analyze the range of variation in them. The results showed a significant increasing trend in the monthly temperature of October (p-value 0.011) and December (p-value 0.05), which is below the alpha value 0.05. Similarly, an increasing trend in annual (p-value 0.000), seasonal (winter p-value 0.008 and summer p-value 0.003), and monthly (January p-value 0.030, April p-value 0.032, June p-value 0.004, July p-value 0.027, and August p-value 0.002) precipitation was observed as computed p-values are less than the significance level of alpha = 0.05. This glaciated region is most vulnerable to climate change because it is already a scarce region in the context of natural resources. Changes in the pattern of precipitation and temperature affect the socioeconomic structure of the region, affecting sectors such as agriculture, livestock, forestry, tourism, and human health. According to the perceptions of people, the temperature rise has accelerated the melting of glaciers and reduced the snow cover area. The increase in rainfall can lead to a higher incidence of mudflows, landslides, floods, and other related events, as the region is made up of sedimentary rocks. Thus, it is crucial to continuously monitor the trends in temperature and precipitation.